2016
DOI: 10.1101/054056
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Large scale chromosome folding is stable against local changes in chromatin structure

Abstract: Characterizing the link between small-scale chromatin structure and large-scale chromosome folding during interphase is a prerequisite for understanding transcription. Yet, this link remains poorly investigated. Here, we introduce a simple biophysical model where interphase chromosomes are described in terms of the folding of chromatin sequences composed of alternating blocks of fibers with different thicknesses and flexibilities, and we use it to study the influence of sequence disorder on chromosome behavior… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…By analyzing human Hi-C data (Dixon et al, 2015), we found evidence that the deleted intra-chromosomal interactions could support BDMR pathogenesis. Our conclusions are further supported by a recent computational polymer model that showed that local chromatin reorganization can happen in scales < 10 5 bp (Florescu et al, 2016).…”
Section: Discussionsupporting
confidence: 85%
“…By analyzing human Hi-C data (Dixon et al, 2015), we found evidence that the deleted intra-chromosomal interactions could support BDMR pathogenesis. Our conclusions are further supported by a recent computational polymer model that showed that local chromatin reorganization can happen in scales < 10 5 bp (Florescu et al, 2016).…”
Section: Discussionsupporting
confidence: 85%
“…We reasoned that because our model assumed a homomorphic fibre, variation between cell types could only arise from differences in the TF binding or CTCF locations as loop extruder anchor sites. However, it is known that chromatin fibres can adopt alternate configurations 1,2,25,26 , and recent RICC-seq experiments suggest there are two main local structural motifs, associated with chromatin fibres: a more open and a more compact conformation 27 . It has also been suggested that acetylation marks regions of disrupted chromatin [27][28][29] , and indeed RICC-seq data showed a more open chromatin structure was correlated with H3K27ac 27 .…”
Section: Polymer Simulations Of Heteromorphic Chromatin Fibres Predicmentioning
confidence: 99%
“…Interestingly, this result coincides with the computational predictions obtained from polymer physics models. Polymer models have predicted that local changes at the scale of unfolding the 30 nm fiber would not affect the larger scale conformations of the chromosome (Florescu et al 2016). These results suggest that fundamental polymer properties of the genome allow local chromatin unfolding without dramatic disruption of larger scale chromosome organization.…”
Section: Discussionmentioning
confidence: 99%